Controle da podridão de raiz (Pythium aphanidermatum) e promoção de crescimento em alface hidropônica - Corrêa, Élida Barbosa (2006)
Due to the characteristics of hydroponic systems, root rot caused by Pythium is limiting for the crop. There are no fungicides registered for this pathossystem and available control techniques are expensive and little efficient. As it is a high-cost system, enhancement of plant growth is imperative. The present work aimed to study the capacity of biological control agents such as Trichoderma sp., Clonostachys rosea, Bacillus subtilis, Paenibacillus lentimorbus and Saccharomyces cerevisiae, and products like P.S.B® Solan, Polyversum® and Fishfértil®, a product based on fermented fish, in a hydroponic system to control root rot caused by Pythium aphanidermatum and to promote lettuce growth. C. rosea, Trichoderma, P. lentimorbus, S. cerevisiae, Polyversum®, P.S.B® and Fishfértil® did not promote lettuce growth in the hydroponic system. The concentrations of 107 conidia/mL of Trichoderma sp.; 10% of culture medium fermented by B. subtilis or not; 250, 500 and 1000g/50L of nutrient solution of biological ferment Itaiquara (S. cerevisiae); and 100, 150 and 250mL/100L of Fishfértil® were harmful to the plant development. A culture medium fermented by B. subtilis in the concentration of 1% promoted lettuce growth. C. rosea controlled the root rot caused by P. aphanidermatum in lettuce grown in hydroponic system and reduced the percentage of recovery of P. aphanidermatum in 29% (first trial) and 43% (second trial) in the treatments with C.rosea, delivered three days before and at the moment of infestation with the pathogen for the first trial and three days before, at the moment and three days after infestation with the pathogen for the second trial.